PERSEPSI WISATAWAN NUSANTARA TERHADAP KUALITAS PELAYANAN DI TMII JAKARTA PASCA REVITALISASI - Rangga Raditya Kepakisan, I Komang Gede; Sudiarta, I Nyoman; Sudana, I Putu (Jurnal IPTA (Industri Perjalanan Wisata), 2025)
This study aims to evaluate the quality of service at Taman Mini Indonesia Indah (TMII) post-revitalization based on the perceptions of domestic tourists.  The research method used is descriptive quantitative, utilizing elements of service quality and involving 100 domestic tourist respondents through purposive sampling and the Hair et al. formula. This study employs two data sources: primary data involving respondent questionnaires, documentation, and observation results, and secondary data obtained from literature or library studies related to the research object. The data analysis techniques used are validity and reliability tests with the aid of a Likert scale. The results of the study show that the quality of service at Taman Mini Indonesia Indah post-revitalization, based on the responses of 100 domestic tourist respondents, obtained an average score of 3.22, which is categorized as "good." Therefore, it can be concluded that the perception of domestic tourists towards the quality of service at Taman Mini Indonesia Indah post-revitalization is satisfactory. This indicates that tourists feel satisfied, safe, and comfortable when visiting Taman Mini Indonesia Indah.